2003
DOI: 10.1097/01.asn.0000040593.93815.9d
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Is a Critical Inhibitor of Calcium Oxalate Crystal Formation and Retention in Renal Tubules

Abstract: Abstract. Calcium nephrolithiasis is the most common form of renal stone disease, with calcium oxalate (CaOx) being the predominant constituent of renal stones. Current in vitro evidence implicates osteopontin (OPN) as one of several macromolecular inhibitors of urinary crystallization with potentially important actions at several stages of CaOx crystal formation and retention. To determine the importance of OPN in vivo, hyperoxaluria was induced in mice targeted for the deletion of the OPN gene together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(192 citation statements)
references
References 44 publications
8
177
1
3
Order By: Relevance
“…(40) We have reported evidence of OPN as a promoter of kidney stone formation (5)(6)(7)(8)(9) ; however, opposing opinions suggest that OPN is an inhibitor. (10)(11)(12) This controversy has not been resolved, but knowledge of stone elimination (13)(14)(15) indicates two possible functions of OPN during kidney stone formation-as a promoter of early crystal conversion to stones and as an inhibitor of kidney stone formation, acting as an opsonin-like molecule involved in crystal digestion by macrophages. Investigation of the crystal elimination process using OPN knockout mice should be continued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(40) We have reported evidence of OPN as a promoter of kidney stone formation (5)(6)(7)(8)(9) ; however, opposing opinions suggest that OPN is an inhibitor. (10)(11)(12) This controversy has not been resolved, but knowledge of stone elimination (13)(14)(15) indicates two possible functions of OPN during kidney stone formation-as a promoter of early crystal conversion to stones and as an inhibitor of kidney stone formation, acting as an opsonin-like molecule involved in crystal digestion by macrophages. Investigation of the crystal elimination process using OPN knockout mice should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using two types of transgenic mice with conversion of the Arg-Gly-Asp (RGD) sequence, the cell-attachment domain of OPN, to the Arg-Gly-Glu (RGE) sequence and lack of two calcium-binding sites consisting of an aspartate chain, we found that each domain could affect the number of kidney CaOx crystals and crystal morphology, respectively, and confirmed OPN function in kidney stone formation as a promoter. (9) However, other reports have demonstrated OPN as an inhibitor of kidney stone formation, (10)(11)(12) although there also have been many studies about the influence of expression change or singlenucleotide polymorphisms (SNPs) of many genes that are related to other stone matrix proteins, urinary high-molecular-weight substances, extracellular matrix, chemotaxis, oxidative stress, cell adhesion, immune reactions, coagulation, oncogene, cell injury, oxalate and calcium metabolism, tubular transporter, lipid metabolism, and so forth. To advance investigations of the genetic background of kidney stone formation, we established a stone-formation mouse model that could become a base of gene recombinant animals (13) and discovered a new phenomenon, stone elimination, during the experimental process.…”
Section: Introductionmentioning
confidence: 99%
“…2) originally identified by us [71]. Moreover, this peptide has been implicated in inhibiting calcification of the urinary tract [32,96] and the motif is also present in salivary statherin and is responsible for maintaining the phosphate/calcium supersaturated mineralization solution dynamics of saliva [5,43,64,78]. Statherin may also function in the transport of calcium and phosphate during secretion in the salivary glands [5,64,78].…”
Section: Introductionmentioning
confidence: 99%
“…Au-delà de son rôle structural, l'OPN inhibe la minéralisation osseuse, sous sa forme phosphorylée [20][21][22]. Elle est, pour cette même raison, un inhibiteur naturel de la formation de lithiase rénale dans le tubule distal [23,24]. L'OPN est impliquée dans de nombreux cancers : sein, côlon, prostate, ostéosarcomes, carcinomes disséminés et mélanomes [25,26].…”
Section: Des Fonctions Physiologiques Et Pathologiques Variéesunclassified
“…Chez ces souris, l'obstruction urétérale s'accompagne d'un infiltrat macrophagique cinq fois moins important que chez les animaux témoins. Par ailleurs, elles présentent une formation anormale de cristaux d'oxalate de calcium dans les tubules rénaux [24]. Les souris OPN -/-présentent une calcification anormale des vaisseaux [32].…”
Section: Phénotypes Rénal Et Cardiovasculaireunclassified